Polycrystalline diamond structure and method for manufacturing the same

A novel PCD structure is created by controlled carbon inclusion in the cemented carbide substrate, addressing fracture and WC plume issues, enhancing mechanical properties and tool life in drilling applications.

CN115038534BActive Publication Date: 2024-12-17ELEMENT SIX (UK) LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080091249.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-31
Filing Date
2020-12-31
Publication Date
2024-12-17
Estimated Expiration
2040-12-31

AI Technical Summary

Technical Problem

Conventional polycrystalline diamond (PCD) cutting elements suffer from issues such as fracture, wear, and the formation of tungsten carbide (WC) plumes at the interface with cemented carbide substrates, leading to reduced performance and short tool life in applications like rock drilling.

Method used

A PCD structure is formed by grinding tungsten carbide powder with a binder containing a large amount of carbon, compacting it to form a green body, sintering in a vacuum, and then bonding diamond grains under ultra-high pressure and temperature to create a cemented carbide substrate with controlled carbon inclusions, minimizing WC plumes and enhancing mechanical properties.

Benefits of technology

The method results in a PCD structure with improved fracture toughness and resistance to impact, reducing the formation of WC plumes and extending tool life in drilling applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115038534B_ABST
    Figure CN115038534B_ABST
Patent Text Reader

Abstract

A polycrystalline diamond structure has a body of polycrystalline diamond (PCD) material; and a cemented carbide substrate bonded to the body of polycrystalline material along an interface. The cemented carbide substrate has tungsten carbide particles bonded together by a binder material, the binder material comprising Co; and the tungsten carbide particles form at least about 70 weight percent and at most about 95 weight percent of the substrate. The cemented carbide substrate has a bulk volume, the bulk volume of the cemented carbide substrate having inclusions of at least about 0.1 vol.% free carbon, the inclusions having a maximum average size in any one or more dimensions of less than about 40 microns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to polycrystalline diamond (PCD) structures and methods of making such structures, and tools incorporating such structures, particularly but not exclusively for use in rock degradation or drilling, or for boring into the earth. Background Art

[0002] Polycrystalline superhard materials such as polycrystalline diamond (PCD) and polycrystalline cubic boron nitride (PCBN) can be used in a wide variety of tools for cutting, machining, drilling or crushing hard or abrasive materials such as rock, metal, ceramic, composite material and wood-containing materials. In particular, tool inserts in the form of cutting elements comprising PCD materials are widely used in drill bits that are drilled into the earth to extract oil or natural gas. The working life of superhard tool inserts may be limited by the fracture (including spalling and chipping) of the superhard material, or by the wear of the tool insert.

[0003] Cutting elements such as those used for rock drill bits or other cutting tool applications typically have a body in the form of a substrate having an interface end / surface and a superhard material that forms a cutting layer bonded to the interface surface of the substrate by, for example, a sintering process. The substrate is generally formed of a tungsten carbide-cobalt alloy (sometimes referred to as cemented tungsten carbide), and the superhard material layer is typically polycrystalline diamond (PCD), polycrystalline cubic boron nitride (PCBN), or a thermally stable product TSP material such as thermally stable polycrystalline diamond.

[0004] Polycrystalline diamond (PCD) is an example of a superhard material (also referred to as a superabrasive or superhard material) that includes a large number of substantially inter-grown diamond grains forming a framework defining interstices between the diamond grains. PCD material typically contains at least about 80% diamond by volume and is conventionally made by subjecting an aggregate of diamond grains to ultra-high pressures, such as greater than about 5 GPa, and temperatures of at least about 1,200° C. The material that fills the interstices in whole or in part may be referred to as a filler or binder material.

[0005] PCD is typically formed in the presence of a sintering aid such as cobalt, which promotes intergrowth of diamond grains. Suitable sintering aids for PCD are also commonly referred to as solvent-catalyst materials for diamond due to their function of dissolving diamond to a certain extent and catalyzing its reprecipitation. Solvent-catalysts for diamond are understood to be materials that are capable of promoting the growth of diamond or direct diamond-to-diamond intergrowth between diamond grains under pressure and temperature conditions at which diamond is thermodynamically stable. Thus, interstices within the sintered PCD product may be filled in whole or in part with residual solvent-catalyst material. Most typically, PCD is often formed on a cobalt-sintered tungsten carbide substrate, which provides a source of cobalt solvent-catalyst for PCD. Materials that do not promote substantial coherent intergrowth between diamond grains may themselves form strong bonds with diamond grains, but are not suitable solvent-catalysts for PCD sintering.

[0006] The sintered tungsten carbide that can be used to form a suitable substrate is formed by mixing tungsten carbide particles / grains and cobalt together and then heating to solidify the carbide particles dispersed in a cobalt matrix. In order to form a cutting element with a superhard material layer (such as PCD or PCBN), diamond particles or grains or CBN grains are placed adjacent to a sintered tungsten carbide body in a refractory metal shell (such as a niobium shell) and subjected to high pressure and high temperature, so that inter-grain bonding between diamond grains or CBN grains occurs, forming a polycrystalline superhard diamond or polycrystalline CBN layer.

[0007] In some cases, the substrate may be fully cured prior to attachment to the superhard material layer, while in other cases the substrate may be green, i.e. not fully cured. In the latter case, the substrate may be fully cured during the HTHP sintering process. The substrate may be in powder form and may be cured during the sintering process used to sinter the superhard material layer.

[0008] The increasing drive for improved productivity in the field of earth drilling has resulted in an increasing demand for materials used to cut rock. Specifically, there is a need for cutting tools with improved resistance to various failure mechanisms to achieve faster cutting rates and longer tool life.

[0009] In the oil and gas drilling industry, cutting elements or tool inserts containing PCD materials are widely used in drill bits that drill into the earth. Rock drilling and other operations require certain mechanical properties, such as high resistance to wear, impact, erosion and corrosion, and high fracture toughness.

[0010] Cutters formed from the most wear resistant grades of PCD material bonded to a cemented carbide substrate are often subject to catastrophic fracture prior to cutter wear because during use of these cutters, cracks grow until they reach a critical length at which catastrophic failure occurs, i.e., when a substantial portion of the PCD and / or cemented carbide substrate fractures. These long, rapidly growing cracks encountered during use of conventional sintered PCD cutters can result in short tool life.

[0011] Furthermore, despite the high strength of polycrystalline diamond (PCD) materials, they are often susceptible to impact fracture due to their low fracture toughness. For example, improving fracture toughness without adversely affecting the material's high strength and wear resistance, which are critical to the material's ability to cut rock, is a challenging task.

[0012] Polycrystalline diamond (PCD) is a superhard (also known as superabrasive) material that includes a large number of intergrown diamond grains and gaps between the diamond grains. PCD can be made by subjecting an aggregate of diamond grains to ultra-high pressure and high temperature. The material that fills the gaps in whole or in part can be referred to as filler material. PCD can be formed in the presence of a sintering aid such as cobalt, which can promote the intergrowth of diamond grains and can also act as a tough, ductile and impact-resistant binder, ensuring a certain degree of PCD fracture toughness. The sintering aid can be referred to as a catalyst / binder material for diamond due to its function of dissolving diamond to a certain extent and catalyzing its reprecipitation. Catalysts / binders for diamond should be understood as materials that can promote the growth of diamond or direct diamond-diamond intergrowth between diamond grains under pressure and temperature conditions where diamond is thermodynamically stable, as well as materials that bind the diamond grains together to form a superhard and tough material. Therefore, the gaps within the sintered PCD product can be filled in whole or in part with residual catalyst / binder material. PCD may be formed on a WC-Co cemented carbide substrate, which may provide a source of cobalt catalyst / binder for the PCD.

[0013] PCD can be used in a wide variety of tools for cutting, machining, drilling or crushing hard or abrasive materials such as rock, metal, ceramic, composite material and wood-containing materials. For example, PCD elements can be used as cutting elements on drill bits used to drill into the earth in the oil and gas drilling industry. Such cutting elements for use in oil and gas drilling applications are typically formed of a layer of PCD bonded to a sintered carbide substrate.

[0014] A known problem with manufacturing conventional PCD cutting elements is related to the formation of large amounts of WC precipitates in the form of flakes (typically referred to in the literature as "WC plumes") at the interface between the body of PCD material and the cemented carbide substrate. The presence of such plumes at the interface leads to a reduction in the performance of the PCD cutting element in different applications. A common view on the cause of the formation of WC plumes is the presence of large amounts of tungsten dissolved in the binder of the conventional cemented carbide substrate. It is well known that the solubility of tungsten in the liquid Co-based binder of cemented carbides is indirectly proportional to the total carbon content (I. Konyashin. Cemented Carbides for Mining, Construction and Wear Parts, Comprehensive Hard Materials, Elsevier Science and Technology, Editor-in-Chief V. Sarin, 2014, 425-251), and therefore, a lower carbon content in the cemented carbide corresponds to a higher amount of tungsten dissolved in the carbide binder. During sintering, as the liquid Co-based binder begins to infiltrate the PCD layers, they become saturated with carbon due to diffusion of carbon from the PCD layers, and the excess tungsten dissolved in the binder precipitates as plate-like WC plumes at the PCD / carbide interface.

[0015] There is therefore a need for a PCD composite structure comprising a body of PCD material bonded to a substrate having good or improved mechanical properties such as fracture toughness and impact resistance, and a method of forming such a composite. Summary of the invention

[0016] Viewed from a first aspect, there is provided a polycrystalline diamond structure comprising:

[0017] a body of polycrystalline diamond (PCD) material; and

[0018] a cemented carbide substrate bonded to the body of polycrystalline material along an interface; wherein

[0019] The cemented carbide substrate comprises tungsten carbide particles bonded together by a binder material, the binder material comprising Co; and

[0020] The tungsten carbide particles form at least about 70 weight percent and at most about 95 weight percent of the substrate;

[0021] wherein the cemented carbide substrate has a bulk volume, the bulk volume of the cemented carbide substrate comprising at least about 0.1 vol. % to about 3 vol. % free carbon, SP 2- Hybridized Carbon or SP 3 - Inclusions of any one or more of hybridized carbon, said inclusions having a maximum average size in any one or more dimensions of less than about 40 microns.

[0022] Viewed from a second aspect there is provided a method of manufacturing a polycrystalline diamond structure according to any one of the preceding claims, the method comprising:

[0023] - grinding tungsten carbide powder with a binder material and a large amount of carbon to form a ground powder, the binder material comprising Co; and the large amount of carbon comprising any one or more of graphite or amorphous carbon in an amount corresponding to an equivalent carbon content (ETC) relative to the ground WC powder that is equal to or greater than about 6.2 wt.%;

[0024] - compacting the ground powder to form a green body;

[0025] - sintering the green body in a vacuum or inert gas atmosphere to form a first pre-composite body;

[0026] - sintering the first pre-composite body to form a sintered carbide substrate;

[0027] - placing the cemented carbide substrate into a canister (cannister) and adding a large amount of diamond grains or particles to form a second pre-sintered assembly; and

[0028] The second pre-sintered assembly is treated in the presence of a catalyst / solvent material for diamond to sinter the diamond grains together to form a polycrystalline diamond compact element at ultra-high pressure of about 6 GPa or more and at a temperature at which diamond material is more thermodynamically stable than graphite.

[0029] Viewed from another aspect there is provided a tool comprising a polycrystalline diamond structure as defined above, the tool being for use in cutting, grinding, grinding, drilling, earth boring, rock drilling or other abrasive applications.

[0030] The tool may include, for example, a drill bit for drilling into the earth or rock, a rotary fixed cutter drill bit for use in the oil and gas drilling industry, or a roller cone drill bit, a hole opening tool, an expansion tool, a borer or other earth boring tool.

[0031] Viewed from another aspect there is provided a drill bit or cutter or component thereof comprising a polycrystalline diamond structure as defined above. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Various variations will now be described by way of example and with reference to the accompanying drawings, in which:

[0033] Figure 1is a schematic perspective view of an example PCD cutter element of a drill bit for boring into the earth;

[0034] Figure 2 is a schematic partial cross-section of an example of a PCD cutter element;

[0035] Figure 3a is an image of the microstructure of a substrate of the example PCD structure prior to sintering with diamond grains to form the example PCD structure;

[0036] Figure 3b After sintering with diamond grains to form the example PCD structure Figure 3a An image of the microstructure of the substrate;

[0037] Figure 4a is an image of the microstructure of a substrate of another example PCD structure prior to sintering with diamond grains to form the example PCD structure;

[0038] Figure 4b After sintering with diamond grains to form the example PCD structure Figure 4a An image of the microstructure of the substrate; and

[0039] Figure 5 is a vertical section of the WC-Co phase diagram through the carbon corner with a cobalt content of 20 mass%.

[0040] illustrate

[0041] As used herein, a "superhard material" is a material having a Vickers hardness of at least about 28 GPa. Diamond and cubic boron nitride (cBN) materials are examples of superhard materials.

[0042] As used herein, "superhard structure" means a structure comprising a body of polycrystalline superhard material. In such a structure, a substrate may be attached thereto.

[0043] As used herein, polycrystalline diamond (PCD) is a type of polycrystalline superhard (PCS) material that includes a plurality of diamond grains, wherein a majority of the diamond grains are directly bonded to one another, and wherein the content of diamond is at least about 80 volume percent of the material. In an exemplary PCD material, the interstices between the diamond grains may be at least partially filled with a binder material that includes a catalyst for diamond. As used herein, "interstices" or "interstitial regions" are regions between the diamond grains of the PCD material. In an exemplary PCD material, the interstices or interstitial regions may be substantially or partially filled with a material other than diamond, or they may be substantially empty. The PCD material may include at least one region from which catalyst material has been removed from the interstices, leaving interstitial voids between the diamond grains.

[0044] The "catalyst material" used for the superhard material can promote the growth or sintering of the superhard material.

[0045] The term "substrate" as used herein means any substrate on which a superhard material layer is formed. For example, the "substrate" as used herein may be a transition layer formed on another substrate.

[0046] As used herein, the term "integrally formed" regions or portions are produced contiguously with each other and are not separated by different kinds of materials.

[0047] In such Figure 1 In the example shown, the cutting element 1 comprises a substrate 10 and a superhard material layer 12 formed on the substrate 10. The substrate 10 may be formed of a hard material such as sintered tungsten carbide. The superhard material 12 may be, for example, polycrystalline diamond (PCD), or a thermally stable product such as thermally stable PCD (TSP). The cutting element 1 may be mounted in a drill bit body such as a drag bit body (not shown) and may be suitable, for example, for use as a cutter insert for a drill bit that is bored into the earth.

[0048] The exposed top surface of the superhard material opposite the substrate forms a cutting face 14 which is the surface that cuts with its edge 16 in use.

[0049] At one end of the substrate 10 is an interface surface 18 that forms an interface with the superhard material layer 12, and the superhard material layer 12 is attached thereto at the interface surface. Figure 1 In the example shown in FIG. 1 , substrate 10 is generally cylindrical and has a peripheral surface 20 and a peripheral top edge 22 .

[0050] As used herein, a PCD grade is a PCD material characterized in terms of the volume content and size of diamond grains, the volume content of interstitial regions between the diamond grains, and the composition of the material that may be present in the interstitial regions. A grade of PCD material may be manufactured by a process comprising providing an aggregate of diamond grains having a size distribution suitable for the grade, optionally introducing a catalyst material or an additive material into the aggregate, and subjecting the aggregate in the presence of a source of catalyst material for diamond to a pressure and temperature at which diamond is more thermodynamically stable than graphite and the catalyst material is molten. Under these conditions, the molten catalyst material may infiltrate the aggregate from the source and may promote direct intergrowth between the diamond grains during sintering to form a PCD structure. The aggregate may contain loose diamond grains or diamond grains held together by a binder material, and the diamond grains may be natural or synthetic diamond grains.

[0051] Different PCD grades may have different microstructures and different mechanical properties such as elastic (or Young's) modulus E, elastic modulus, transverse rupture strength (TRS), toughness (such as so-called K1C toughness), hardness, density and coefficient of thermal expansion (CTE). Different PCD grades may also behave differently in use. For example, different PCD grades may have different wear rates and fracture resistance.

[0052] All PCD grades may include interstitial regions filled with a material comprising cobalt metal, an example of a catalyst material for diamond.

[0053] The PCD structure 12 may include one or more PCD grades.

[0054] Figure 2 is a cross section of PCD material that may be formed in an example tool Figure 1 The superhard layer 2. In the formation process of conventional polycrystalline diamond structures, diamond grains 22 are directly bonded to adjacent grains, and the gaps 24 between the grains 22 of superhard material (such as diamond grains in the case of PCD) may be at least partially filled with non-superhard phase material. This non-superhard phase material, also known as filler material, can include residual catalyst / binder material, such as cobalt, nickel or iron.

[0055] Reference Figures 3a to 5 Example PCD structures are further described. Examples of such PCD structures include a body of polycrystalline diamond material (PCD) bonded to a cemented carbide substrate along an interface. The cemented carbide substrate includes tungsten carbide particles bonded together by a binder material, the binder material comprising, for example, Co. The tungsten carbide particles form at least about 70 weight percent and at most about 95 weight percent of the substrate. The entire volume of the sintered carbide substrate includes at least about 0.1 vol.% to about 3 vol%, or to about 2.5 vol%, or to about 2 vol% free carbon, SP 2 - Hybridized Carbon or SP 3 - Inclusions of any one or more of hybridized carbon such as graphite and / or diamond, said inclusions having a maximum average size in any one or more dimensions of less than about 40 microns.

[0056] In some instances, the inclusions have an average size of less than about 30 microns, and in other instances the inclusions have an average size of less than about 10 microns.

[0057] In some examples, the entire volume of the cemented carbide substrate can include at least about 0.3 vol. % inclusions.

[0058] In some examples, the binder material of the substrate may include up to about 50 wt. % Fe.

[0059] In further examples, the binder material of the substrate comprises between about 0.1 to about 4 wt. % tungsten and between about 0.05 to about 5 wt. % carbon in solid solution, and in other examples, the binder material comprises at least about 0.1 weight percent to at most about 5 weight percent of any one or more of V, Ta, Ti, Mo, Zr, Nb, Hf in solid solution or carbide phase form.

[0060] The binder material may include at least about 0.1 weight percent and at most about 2 weight percent of any one or more of Re, Ru, Rh, Pd, Re, Os, Ir, and Pt in solid solution.

[0061] For example, the cemented carbide substrate may have a thickness from the interface with the body of PCD material of at least about 0.1 mm, or at least about 0.2 mm, or at least about 0.3 mm.

[0062] In additional examples, a second cemented carbide substrate may be bonded to the cemented carbide substrate along a second interface opposite the interface with the body of PCD material, the second substrate comprising substantially no free carbon, SP 2 - Hybridized Carbon or SP 3 - Inclusions of any one or more of hybrid carbons.

[0063] In some examples, the interface region between the cemented carbide substrate and the body of PCD material comprises substantially no plate-like WC grains.

[0064] Example polycrystalline diamond structure can be made by grinding tungsten carbide powder with binder material and a large amount of carbon to form a ground powder, the binder material includes Co, and a large amount of carbon includes any one or more of graphite or amorphous carbon, and its amount corresponds to an equivalent carbon content (ETC) relative to the ground WC powder is equal to or greater than about 6.2wt.%. Compact the ground powder to form a green body, which is then sintered in a vacuum or inert gas atmosphere to form a first pre-composite. The first pre-composite is then sintered to form a sintered carbide substrate. The sintered carbide substrate is placed in a can and a large amount of diamond grains or particles are added to form a second pre-sintered assembly. Subsequently, at about 6GPa or higher, such as about 6.8GPa, or about 7GPa, or about 7.7Pa, or 8GPa or higher ultra-high pressure and diamond material is more thermodynamically stable than graphite, the second pre-sintered assembly is processed in the presence of a catalyst / solvent material for diamond to sinter the diamond grains together to form a polycrystalline diamond composite sheet element. The bulk volume of the substrate of the PCD structure so formed has at least about 0.1 vol. % inclusions of free carbon, such as graphite, having a maximum average size in any one or more dimensions of less than about 40 microns.

[0065] The step of sintering the green body to form the pre-composite body may include heating the green body to a temperature of at least about 300° C. in a vacuum and then annealing the green body for at least about 5 minutes.

[0066] In some examples, prior to the step of placing the cemented carbide substrate in the can, a sintered carbide disk having a thickness of at least about 2 mm may be formed, the disk comprising a binder material comprising Co and at least about 0.1 vol. % carbon inclusions in the form of graphite. Additional cemented carbide pillars having a binder material comprising, for example, Co may also be formed, and the disk and pillars may then be bonded together by sintering at ambient conditions or under ultra-high pressure to form an example sintered carbide substrate for placement in the can with a plurality of diamond grains or particles.

[0067] In such examples, the ground powder can be pressed onto or around a sintered carbide column having a binder material including, for example, Co to form a green body; and the step of sintering the green body can, for example, include sintering the column with a layer of the ground powder in a vacuum or protective gas at a temperature in a range between about 1350° C. and about 1400° C. for between about 10 and about 60 minutes.

[0068] In an alternative example, the step of bonding the disk and the post may include brazing, for example by placing a barrier interlayer between the post and the disk, the barrier layer having a thickness of at least about 10 μm and comprising any one or more of a metal, a metal carbide, a nitride or a carbonitride.

[0069] In any one or more of the example methods, after the step of sintering the first pre-composite body to form a cemented carbide substrate, the method may further include the step of selectively decarburizing a portion of the sintered carbide substrate at a temperature of at least about 700° C. in a hydrogen atmosphere or a CO2 atmosphere for at least about 1 hour, the portion having a thickness of at least about 50% of the total height of the sintered carbide substrate.

[0070] In any one or more of the example methods, after the step of sintering the first pre-composite body to form a cemented carbide substrate, the method may further include carburizing the cemented carbide substrate at a temperature of at least about 1350° C. for between about 1 hour and about 10 hours in an atmosphere including any one or more of a hydrocarbon gas, an inert gas, or hydrogen.

[0071] The carburizing step may include treating the cemented carbide substrate or green body with a powder mixture comprising any one or more of carbon black, graphite, or a carbon-containing precursor in an atmosphere comprising any one or more of an inert gas, hydrogen, or a gas mixture comprising hydrocarbons at a temperature greater than about 1000° C. for at least about 1 hour.

[0072] In some examples, the step of treating the second pre-sintered assembly includes subjecting the assembly to a temperature sufficiently high that the catalyst / solvent is in a liquid state and a first pressure at which diamond is thermodynamically stable, reducing the first pressure to a second pressure at which diamond is thermodynamically stable, maintaining the temperature sufficiently high to keep the catalyst / binder in a liquid state, reducing the temperature to solidify the catalyst / binder and then reducing the pressure and temperature to ambient conditions to form a body of example polycrystalline diamond material bonded to the cemented carbide substrate.

[0073] A PCD structure according to any of the examples may be included in or used as a tool for cutting, grinding, grinding, drilling, earth drilling, rock drilling or other abrasive applications, such as a drill bit for earth drilling or rock drilling. A tool including an example PCD structure may include a rotary fixed cutting edge drill bit for use in the oil and gas drilling industry, such as a roller cone drill bit, a hole opening tool, an expansion tool, a drill or another earth boring tool. A drill bit or cutter or a component thereof may include any one or more of the example PCD structures.

[0074] Reference is made below to the following examples (which are not intended to be limiting) and to Figure 5 Discuss in more detail Figures 3a to 4b Formation of an example of a PCD structure is shown.

[0075] A control batch of conventional sintered carbide substrates for PCD structures was produced by forming 5 kg of a powder mixture by grinding WC powder having an average grain size of about 1.3 μm, Co powder having an average grain size of almost 1 μm, together with 30 kg of carbide balls and 100 g of paraffin wax in a ball mill. Once the powder was dry, it was granulated and compacted to form a substrate for PCD structures in green form. The equivalent total carbon (ETC) in the sintered carbide material was determined to be about 6.12 percent relative to WC.

[0076] Greenware by Sinterhip TM The furnace was sintered at 1,420° C. for about 75 min, of which 45 min were carried out in vacuum and 30 min were carried out in Ar at a pressure of about 40 bar in the HIP apparatus.

[0077] Thereafter, a layer of polycrystalline diamond is bonded to each control carbide substrate by placing each substrate separately in a can and adding a large amount of diamond grains or particles to form a second pre-sintered assembly. The second pre-sintered assembly is then treated at an ultra-high pressure of about 6 GPa or more, in some examples about 7 GPa or more, and at a temperature of about 1400°C in the presence of a catalyst / solvent material for diamond to sinter the diamond grains together to form a polycrystalline diamond structure.

[0078] Example 1

[0079] An experimental batch of carbide substrates for a first example PCD structure was produced using the same procedure described above for the control batch, except that 0.2 wt.% carbon was added to the powder mixture to be ground. In this first example, the equivalent total carbon (ETC) in the sintered carbide material was determined to be 6.32 percent relative to WC.

[0080] Thereafter, a layer of polycrystalline diamond was bonded to the carbide substrate using the high pressure and high temperature (HPHT) procedure described above to produce a first set of examples of PCD structures.

[0081] Example 2

[0082] Another experimental batch of carbide substrates for forming the second example PCD structure was produced using the same procedure described above for the control batch, except that 0.5 wt.% carbon was added to the powder mix to be milled. The equivalent total carbon (ETC) in the sintered carbide material was determined to be 6.62 percent relative to WC.

[0083] Thereafter, a layer of polycrystalline diamond was bonded to the carbide substrate using the high pressure and high temperature (HPHT) procedure described above to produce a second set of examples of PCD structures.

[0084] The magnetic coercivity and other properties of the control carbide substrate and the example carbide substrate were determined using conventional procedures. In particular, the control carbide substrate was found to have a magnetic coercivity equal to about 170 Oe and a magnetic moment equal to 13.2 Gcm 3 / g and the density is equal to 14.15g / cm 3 .

[0085] In contrast, for the structure formed according to Example 1, the carbide substrate was found to have a magnetic coercivity equal to approximately 169 Oe and a magnetic moment equal to 13.6 Gcm 3 / g and density equals 14.0g / cm 3 .

[0086] For the structure formed according to Example 2, the carbide substrate was found to have a magnetic coercivity equal to about 170 Oe and a magnetic moment equal to 13.7 Gcm 3 / g and the density is equal to 14.0g / cm3.

[0087] To investigate the mechanical properties of the control carbide substrate, the PCD layer was removed by EDM cutting. The Vickers hardness of the substrate was determined to be equal to HV 20 =1230, the transverse rupture strength is determined to be 3700MPa, and the indentation fracture toughness is determined to be 15.3MPa m 1 / 2 .

[0088] To investigate the mechanical properties of the carbide substrates formed according to Example 1, these substrates were tested under the same conditions as the control substrates after the PCD layer was removed by EDM cutting. The Vickers hardness of the substrate of Example 1 was determined to be equal to HV 20 =1240, the transverse rupture strength is determined to be 2860MPa, and the indentation fracture toughness is determined to be 15.5MPa m 1 / 2 .

[0089] To investigate the mechanical properties of the carbide substrates formed according to Example 2, these substrates were tested under the same conditions as the control substrates after the PCD layer was removed by EDM cutting. The Vickers hardness of the substrates formed according to Example 2 was determined to be equal to HV 20 = 1250, the transverse rupture strength was determined to be 3040 MPa, and the indentation fracture toughness was determined to be about 19 MPa m 1 / 2 .

[0090] In addition to mechanical properties, the microstructure of the control substrates and substrates produced according to Examples 1 and 2 above were studied using conventional high resolution TEM and / or SEM procedures and again after initial sintering of the substrates and after the sintering stage used to form the PCD structure in which the diamond grains were sintered and bonded to the substrate.

[0091] The microstructure of the control carbide substrate was found to be free of free carbon and eta-phase both before and after the second sintering when studied using conventional high resolution TEM and SEM procedures.

[0092] Figure 3a and 3b The images of the microstructure of the structure formed according to Example 1 before and after the second sintering are shown respectively. Figure 3a It can be seen that before the second sintering stage, the microstructure was found to include inclusions of free carbon and Figure 3b As can be seen in the Figure 1, after the second sintering to form the PCD structure of Example 1, the microstructure includes significantly fewer inclusions of free carbon than before the second HPHT procedure, and they are finely and evenly distributed in the microstructure. Again using standard TEM procedures, the substrate of the Example PCD structure Figure 3b The volume percentage of free carbon inclusions shown in was determined to be about 0.4 vol. %, and these free carbon inclusions had a maximum average size in any one or more dimensions of less than about 40 microns.

[0093] Figure 4a and 4b The images of the microstructure of the structure formed according to Example 2 before and after the second sintering are shown respectively. Figure 4a It can be seen that before the second sintering stage, the microstructure of the substrate was found to include inclusions of free carbon and Figure 4b As can be seen in Figure 2, after the second sintering to form the PCD structure of Example 2, the microstructure of the example substrate includes significantly fewer inclusions of free carbon than before the second HPHT procedure, and they are finely and evenly distributed in the microstructure. Again using standard SEM procedures, in the example PCD structure Figure 4b The volume percentage of inclusions of free carbon in the example substrate shown in was determined to be about 1.3 vol. %, and the inclusions of free carbon in the example substrate had a maximum average size in any one or more dimensions of less than about 40 microns.

[0094] Image analysis also showed that for the example PCD structures, no WC platelets ("feathers") were found at the interface of the bulk of the PCD material and the substrate.

[0095] It can thus be seen that the PCD structures formed according to Examples 1 and 2 show a favourable combination of mechanical properties including significantly improved fracture toughness over the control PCD structure. While not wishing to be bound by any particular theory, it is believed that this may be due to or aided by at least the unexpected and unusual microstructure of the substrate in the example PCD structures, which is seen to include fine carbon inclusions less than 40 microns in any largest dimension and which is distributed throughout a substantial portion of the substrate and in some examples is in a substantially uniform or uniform distribution.

[0096] Conventional teaching regarding the effect of free carbon precipitates on the mechanical properties of cemented carbides is that the presence of such precipitates in the cemented carbide microstructure significantly reduces the hardness, toughness and transverse rupture strength (TRS) of the carbide structure (see, e.g., Suzuki, H., Kubota, H., entitled The influence of binder phase composition on the properties of tungsten carbide-cobalt cemented carbides, Planseeberichte fuer Pulvermetallurgie 14(2), (1966) 96-109). However, the present applicants have unexpectedly discovered that the example structures formed by the example methods, which bond a body of PCD material to a cemented carbide substrate having an overall volume comprising at least about 0.1 vol.% inclusions of free carbon having a maximum average size in any one or more dimensions of less than about 40 microns, act synergistically and unexpectedly to significantly improve fracture toughness over control PCD structures. While not wishing to be bound by any particular theory, a possible explanation may be that the applicants have discovered that the solubility of carbon in the liquid binder increases significantly under ultra-high pressures, and that when a large amount of free carbon is present in the form of a sintered carbide substrate prior to the second sintering stage, the fracture toughness of the PCD structure is improved. Figure 3a and 4a When present in the microstructure in the form of large graphite inclusions as seen in , these are likely to dissolve in the liquid binder during the second sintering stage, i.e. during the PCD sintering stage. As a result of solidification after the PCD sintering stage, excess carbon is precipitated in the substrate in the form of very fine and uniformly distributed particles, e.g. Figure 3b and 4b As shown, quite surprisingly, this does not appear to have a detrimental effect on the mechanical properties of the PCD structure.

[0097] Furthermore, it was found that the formation of WC plumes can be suppressed by the example method of forming the example PCD structure.

[0098] Additionally, it is believed that the example method and in particular the addition of a large amount of carbon prior to sintering may have desirable sintering aid properties. While not wishing to be bound by theory, a possible explanation may be that if the liquid binder is saturated or supersaturated with carbon during the PCD press sintering process, according to Figure 5The W-Co-C phase diagram shown has a lower melting point (see B. Uhrenius, H. Pastor, E. Pauty, on The composition of Fe-Ni-Co-WC-based cemented carbides, Int. J Refractory Met Hard Mater., 15 (1997) 139-149). As a result, when the temperature of the PCD press sintering is increased, the solid densification ratio of the diamond abrasive grain obtained before the binder melts is reduced, and the penetration of the PCD slice by the liquid binder may occur earlier in the sintering cycle than with conventional sintering techniques, resulting in improved sintering.

[0099] While various examples have been described with reference to a number of examples, those skilled in the art will appreciate that various changes may be made and equivalents may be substituted for elements thereof, and that the examples are not intended to be limited to the specific examples disclosed. In particular, while standard SEM and TEM imaging techniques may be used to determine the vol% of inclusions, conventional optical microscopy techniques may also be used.

Claims

1. A polycrystalline diamond structure comprising: A body of polycrystalline diamond material; as well as a cemented carbide substrate bonded along an interface to the body of polycrystalline diamond material; in The cemented carbide substrate comprises tungsten carbide particles bonded together by a binder material, the binder material comprising Co; and The tungsten carbide particles form 70 weight percent to 95 weight percent of the substrate; The sintered carbide substrate has a bulk volume, wherein the bulk volume of the sintered carbide substrate includes 0.1 vol. % to 3 vol. % of free carbon, SP 2 - Hybridized Carbon or SP 3 - Inclusions of any one or more of hybridized carbon, said inclusions having a maximum average size in any one or more dimensions of less than 40 micrometers.

2. The polycrystalline diamond construction of claim 1, the inclusions in the bulk volume of the cemented carbide substrate having an average size of less than 30 microns.

3. The polycrystalline diamond construction of claim 1, the inclusions in the bulk volume of the cemented carbide substrate having an average size of less than 10 microns.

4. The polycrystalline diamond structure of claim 1, wherein: The entire volume of the cemented carbide substrate includes 0.3 vol. % to 3 vol % of the inclusions.

5. The polycrystalline diamond structure of claim 1, wherein: The inclusions form 0.1 vol% to 2.5 vol% of the entire volume of the cemented carbide substrate.

6. The polycrystalline diamond structure of claim 1, wherein: The inclusions form 0.1 vol% to 2 vol% of the entire volume of the cemented carbide substrate.

7. The polycrystalline diamond structure of claim 1, wherein: The inclusions include any one or more of graphite and diamond.

8. The polycrystalline diamond structure of claim 1, wherein: The binder material of the substrate comprises up to 50 wt. % Fe.

9. The polycrystalline diamond structure of claim 1, wherein: The binder material contains between 0.1 and 4 wt.% tungsten and between 0.05 and 5 wt.% carbon in solid solution.

10. The polycrystalline diamond structure of claim 1, wherein: The binder material contains 0.1 to 5 weight percent of any one or more of V, Ta, Ti, Mo, Zr, Nb, and Hf in the form of a solid solution or a carbide phase.

11. The polycrystalline diamond structure of claim 1 , wherein: The binder material contains 0.1 to 2 weight percent of any one or more of Re, Ru, Rh, Pd, Os, Ir, and Pt in solid solution.

12. The polycrystalline diamond structure of claim 1, wherein: The cemented carbide substrate has a thickness of at least 0.1 mm from the interface with the body of polycrystalline diamond material.

13. The polycrystalline diamond structure of claim 1, wherein: The cemented carbide substrate has a thickness of at least 0.2 mm from the interface with the body of polycrystalline diamond material.

14. The polycrystalline diamond structure of claim 1, wherein: The cemented carbide substrate has a thickness of at least 0.3 mm from the interface with the body of polycrystalline diamond material.

15. The polycrystalline diamond construction of claim 1 further comprising a second cemented carbide substrate bonded to the cemented carbide substrate along a second interface opposite the interface of the body of polycrystalline diamond material, the second cemented carbide substrate being free of inclusions of free carbon.

16. The polycrystalline diamond structure of claim 1, wherein: The interface region between the cemented carbide substrate and the body of polycrystalline diamond material does not include plate-like WC grains.

17. A method of manufacturing a polycrystalline diamond structure according to claim 1, the method comprising: - grinding tungsten carbide powder with a binder material and a large amount of carbon to form a ground powder, the binder material comprising Co; and the large amount of carbon comprising any one or more of graphite or amorphous carbon, the amount corresponding to an equivalent carbon content ETC relative to the ground WC powder being equal to or greater than 6.2 wt.%; - compacting the ground powder to form a green body; - sintering the green body in a vacuum or inert gas atmosphere to form a first pre-composite body; - sintering the first pre-composite body to form a sintered carbide substrate; - placing the cemented carbide substrate into a can and adding a plurality of diamond grains or particles to form a second pre-sintered assembly; and - treating the second pre-sintered assembly in the presence of a catalyst / solvent material for diamond at an ultra-high pressure of 6 GPa or more and at a temperature at which diamond material is more thermodynamically stable than graphite to sinter the diamond grains or particles together to form a polycrystalline diamond structure as claimed in claim 1.

18. The method according to claim 17, wherein: The step of sintering the green body to form the pre-composite body comprises heating the green body to a temperature of at least 300° C. in a vacuum and then annealing the green body for at least 5 minutes.

19. The method of claim 17, further comprising, before the step of placing the cemented carbide substrate in the can, forming the cemented carbide substrate by: - forming a sintered carbide disk having a thickness of at least 2 mm, said disk comprising a binder material comprising Co and at least 0.1 vol.% of carbon inclusions in the form of graphite; - forming additional cemented carbide pillars with a binder material comprising Co; and - bonding said disc and said pillar together by sintering at ambient conditions or under ultra-high pressure to form said cemented carbide substrate for placement into said canister with said plurality of diamond grains or particles.

20. The method of claim 17, further comprising pressing the ground powder onto or around a cemented carbide column having a binder material comprising Co to form the green body; and wherein The step of sintering the green body comprises sintering the column with a layer of the ground powder at a temperature ranging between 1350° C. and 1400° C. for between 10 and 60 minutes in vacuum or protective gas.

21. The method according to claim 19, wherein: The step of bonding the disk and the post includes brazing the disk to the post to bond the disk and the post together.

22. The method according to claim 21, wherein: The brazing step includes placing a barrier interlayer between the post and the disk, the barrier layer having a thickness of at least 10 μm and comprising any one or more of a metal, a metal carbide, a nitride or a carbonitride.

23. The method of claim 17, further comprising, after the step of sintering the first pre-composite body to form the cemented carbide substrate, selectively decarburizing a portion of the sintered carbide substrate at a temperature of at least 700° C. in a hydrogen atmosphere or a CO2 atmosphere for at least 1 hour, the portion having a thickness of at least 50% of the total height of the sintered carbide substrate.

24. The method of claim 17, further comprising carburizing the cemented carbide substrate at a temperature of at least 1350° C. for between 1 hour and 10 hours in an atmosphere including any one or more of a hydrocarbon gas, an inert gas, or a hydrogen gas after the step of sintering the first pre-composite body to form the cemented carbide substrate.

25. The method of claim 17, further comprising carburizing the green body at a temperature of at least 1350°C for between 1 hour and 10 hours in an atmosphere comprising any one or more of hydrocarbon gas, hydrogen gas or an inert gas.

26. The method of claim 17, further comprising carburizing the green body with a powder mixture comprising any one or more of carbon black, graphite, or a carbon-containing precursor at a temperature above 1000°C for at least 1 hour in an atmosphere comprising any one or more of an inert gas, hydrogen, or a gas mixture comprising hydrocarbons.

27. The method of claim 17, further comprising carburizing the cemented carbide substrate with a powder mixture comprising any one or more of carbon black, graphite, or a carbon-containing precursor in an atmosphere comprising any one or more of an inert gas, hydrogen, or a gas mixture comprising hydrocarbons at a temperature greater than 1000° C. for at least 1 hour after the step of sintering the first pre-composite body to form the cemented carbide substrate.

28. The method of claim 17, wherein: The steps of processing the second pre-sintered component include: - subjecting the assembly to a sufficiently high temperature at which the catalyst / solvent is in a liquid state and a first pressure at which diamond is thermodynamically stable; - reducing said first pressure to a second pressure at which diamond is thermodynamically stable, said temperature being maintained high enough to keep said catalyst / binder in a liquid state; - reducing the temperature to allow the catalyst / binder to cure; and - reducing the pressure and the temperature to ambient conditions to form a body of polycrystalline diamond material bonded to the cemented carbide substrate.

29. A tool comprising a polycrystalline diamond construction according to claim 1, the tool being used for cutting, grinding, grinding, drilling, earth boring, rock drilling or other abrasive applications.

30. The tool of claim 29, wherein: The tool comprises a drill bit for drilling into the earth or rock.

31. The tool of claim 29, wherein: The tool comprises a rotary fixed cutter drill bit for use in the oil and gas drilling industry.

32. The tool of claim 29, wherein: The tool is a hole opening tool, an expansion tool or another earth boring tool.

33. The tool of claim 32, wherein: The hole-making tool is a roller cone drill or a drill.

34. A drill bit or cutter or a component thereof comprising a polycrystalline diamond construction according to claim 1.